Low-income consumers and payment choice - Oz Shy (Federal Reserve Bank of Atlanta, 2020)
Low-income consumers are not only constrained with spending, but also with the type and variety of payment methods available to them. Using a representative sample of the U.S. adult population, this paper analyzes the low possession (adoption) of credit and debit cards among lowincome consumers who are also unbanked. Using a random utility model, I estimate the potential welfare gains associated with policy options suggested in the literature to provide subsidized and unsubsidized debit cards to this consumer population.
Keywords: D9; E42; 330; consumer payment choice; household income; financial inclusion; unbanked consumers; random utility analysis